(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
After the Spanish Presidential Elections held last November 20th 2011, which the Popular Party won with a clear majority, raised the possibility of advancing the legal and constitutional deadlines for the investment of the candidate for prime minister. The approach, unprecedented in our democratic history, was based on the assumption that the normal interval between the conclusion of the elections and the investment of the candidate, of about one month, could lead to a worsening of the economic unsteadiness, due to a political deadlock in decision-making. Through this article we will show that, indeed, in the case of the general elections, as in generic terms, it is indeed possible to shorten the term for the investment.